2001
DOI: 10.1007/s002100000339
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Dopamine receptors in human platelets

Abstract: The expression of dopamine receptors by human platelets was investigated by Western blot analysis and immunocytochemical techniques using antibodies raised against dopamine D1-D5 receptor protein. The influence of dopamine D1-like and D2-like receptor agonists on adrenaline-induced platelet aggregation was also investigated. Western blot analysis revealed that platelet membranes bind anti-dopamine D3 or D5 receptor protein antibodies, but not anti-D1, D2 or D4 receptor protein antibodies. Cytospin centrifuged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…[33][34][35][36][37][38] Additionally, there are several blood coagulation pathways involving D 3 receptors systems, including the activation of platelet aggregation and the secretion of the procoagulant von Willebrand factor. 39,40 Hence, D 3 receptors blockade could also predispose the patient to the formation of acute thrombosis in stenotic coronary arteries, contributing to AMI.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38] Additionally, there are several blood coagulation pathways involving D 3 receptors systems, including the activation of platelet aggregation and the secretion of the procoagulant von Willebrand factor. 39,40 Hence, D 3 receptors blockade could also predispose the patient to the formation of acute thrombosis in stenotic coronary arteries, contributing to AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the G␣ s -coupled ␣ 2A adrenoreceptor is reported to inhibit platelet serotonin release (39). The expression of dopamine receptors (D 3 type) in platelets was recently published (40). Preloading of intact Tph1Ϫ/Ϫ platelets was performed with either serotonin or noradrenaline in the absence or presence of spiperone, which blocks 5HT 2A and D 2 -like receptors, BRL 44408, which interferes with ␣ 2A receptors, and GR 103691, antagonizing D 3 receptor-mediated effects at 100 nM each.…”
Section: Down-regulation Of Vmat2 By G␣ Q Does Not Involve Plasmamentioning
confidence: 99%
“…Human platelets, a mammalian cell model Human platelets have long been thought to lack D 2 receptors [143], which are the primary target for antipsychotic drugs. However, it has recently been reported that human platelets contain D 2 -like receptors that mediate potentiation of ADP-induced aggregation [149].…”
Section: Human Plateletsmentioning
confidence: 99%